THE GREENHOUSE GAS ANALYSIS USING LIFE CYCLE ASSESSMENT (LCA) IN SMALL SCALE TOFU INDUSTRY - Nugraha, Aditya Wahyu; Larassati, Dyah Putri; Wulandari, Annisa Dwi (Jurnal Teknologi Industri Pertanian, 2024)
The tofu industry is one of the industries that has grown and developed a lot in Indonesia to meet the community's food needs. In the tofu production cycle, many activities have the potential to produce emissions that are harmful to the environment, one of which is greenhouse gases (GHGs). There are various activities carried out by the tofu industry to produce products that are ready for sale, starting from the procurement of raw materials, the production and distribution of tofu to the market. The longer the tofu production chain, the greater the potential to produce GHG emissions. To find out the amount of GHG emissions produced, it is necessary to take a tofu product life cycle (LCA) assessment. Therefore, this study aims to calculate the GHG emissions produced in the tofu production cycle in the X’s tofu industry. The results show that X’s tofu industry produces GHG emissions of 3,373.53 KgCO2eq per 300 kg soybean which originate from the use of electricity, gasoline, firewood, and liquid waste. Every activity carried out also contributes to the emergence of GHG emissions. The highest GHG comes from the use of firewood of 3,198.81 KgCO2eq, meanwhile, the stage that generates the most GHG is during the cooking stage. Alternative improvements that can be made to reduce emissions are minimizing the use of transportation equipment, minimizing water usage (water reduction), water reuse, converting the use of firewood to LPG, and utilizing liquid waste into biogas for the cooking process. Keywords: emission, greenhouse gas (GHG), life cycle assessment (LCA), tofu industry